When Disfluency Signals Competence: The Effect of Processing Difficulty on Perceptions of Service Agents - Thompson, Debora V.; Ince, Elise Chandon (Journal of Marketing Research, 2013)
This research examines the effect of processing fluency on judgments of agent competence. In the context of service relationships, four studies reveal that the experience of processing difficulty, or disfluency, enhances expectations of agent-exerted effort and competence, which in turn increase expected service value. When reading information about a target service, consumers interpret the difficulty of processing information as a signal of the level of skill required to execute the task, which highlights the agent's expected utility. The authors explore several moderators of this positive effect of disfluency, showing that it is attenuated under conditions that decrease the relevance of consumers’ subjective experiences and it may be reversed on measures of experienced (vs. expected) service value.